Green Banking: Operating Costs on Operating Income, Capital Adequacy Ratio, Financial Slack, Sustainability Officer, and Sustainability Committee - Ihsan Mulia Siregar; Slamet Haryono (Universitas Airlangga, 2023)
ABSTRACT This study aims to investigate and analyze e the effect of Operating Expenses Operating Income (BOPO), capital adequacy ratio (CAR), financial slack, sustainability officer, and sustainability committee on green banking disclosure in Islamic banks registered with the Financial Services Authority (OJK) during the period 2017-2021. In this study, panel data regression data analysis techniques were used with the help of Eviews 10 software. The results of this study show that partially the variables Operating costs in operating income (BOPO), capital adequacy ratio (CAR), financial slack, and sustainability officer have no effect on green banking disclosure. While the variable Sustainability Committee has a positive and significant effect on Green Banking disclosure. At the same time, the variables BOPO, CAR, Financial Slack, Sustainability Officer, and Sustainability Committee have a significant effect on Green Banking disclosure. The implication of this research for science is to contribute to the literature related to the factors that influence green banking disclosure. In addition, this research is also expected to help banks in improving their governance, and for the government is expected to help in making policies related to green banking disclosure. Keywords: Operating Expenses on Operating Income, Capital Adequacy Ratio, Financial Slack, Green Banking, Sustainability ABSTRAK Penelitian ini bertujuan untuk mengkaji dan menganalisis pengaruh dari Biaya Operasional Pendapatan Operasional (BOPO), Rasio Kecukupan Modal (CAR), Financial Slack, Sustainability Officer, dan Sustainability committee terhadap pengungkapan green banking pada bank syariah yang terdaftar di OJK selama periode 2017-2021. Teknik sampling yang digunakan adalah Purposive Sampling dengan kriteria tertentu, sehingga sampel didapat sebanyak 45 data dari 9 Bank syariah yang sesuai kriteria. Dan menggunakan teknik analisis data regresi data panel dengan bantuan software Eviews 10. Hasilnya menunjukkan bahwa secara parsial variabel BOPO, Capital Adequacy Ratio (CAR), Financial Slack dan Sustainability Officer tidak berpengaruh terhadap pengungkapan Green banking. Sedangkan variabel Sustainability Committee berpengaruh positif dan signifikan terhadap pengungkapan Green Banking. Secara simultan variabel BOPO, CAR, Financial Slack, Sustainability officer dan Sustainability Committee memiliki pengaruh dan signifikan terhadap pengungkapan Green banking Kata Kunci: Biaya Operasi pada Pendapatan Operasional, Capital Adequacy Ratio, Financial Slack, Green Banking, Sustainability